2000
DOI: 10.1074/jbc.275.19.14457
|View full text |Cite
|
Sign up to set email alerts
|

A 56-kDa Selenium-binding Protein Participates in Intra-Golgi Protein Transport

Abstract: Transport of proteins between intracellular membrane compartments is a highly regulated process that depends on several cytosolic factors. By using the well characterized intra-Golgi cell-free transport assay, we purified from bovine brain cytosol a 56-kDa protein that shows a significant transport activity. Partial sequencing of four tryptic peptides obtained from the 56-kDa protein revealed its identity to a cytosolic protein previously characterized as a selenium-binding protein, SBP56. Recombinant SBP56 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 58 publications
3
104
0
6
Order By: Relevance
“…The transport reactions were incubated for 2 h at 30°C. The incorporation of N-[ 3 H]acetylglucosamine into the VSV-G protein was determined as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
“…The transport reactions were incubated for 2 h at 30°C. The incorporation of N-[ 3 H]acetylglucosamine into the VSV-G protein was determined as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
“…SELENBP1 is a cytoplasmic protein, but a significant amount of SELENBP1 was also membrane associated, predominantly on the Golgi membrane. 18 To validate our findings, SELENBP1 protein levels in the membrane fraction of HOSE and cancer cells were assayed with the SELENBP1-specific antibody. As expected, SELENBP1 was detected in the HOSE cells (Fig.…”
Section: Selenbp1 Protein Identification and Verificationmentioning
confidence: 99%
“…SELENBP1 is implicated to play a role in toxification/ detoxification processes (257), cell-growth regulation (21,119), intra-Golgi protein transport (255), aging (71), and lipid metabolism (251). Interestingly, several studies have reported decreased expression levels of both SELENBP1 and SELENBP2 in tumors compared with normal tissue.…”
Section: G Selenium-binding Proteinsmentioning
confidence: 99%